Curious Vascular Tumor - Faissal Jghaimi; Hasna Baallal; Anas Fakhri; Hanane Rais; Noama Karbout; Nadia Akhdari; Said Amal; Badia Belaabidia (Hindawi Limited, 2012)
Introduction. Sinusoidal hemangioma is a rare variant of acquired cavernous hemangioma predominantly occurring in females. Very few case reports have been described in the literature. Case Report. We present a case of a 46-year-old woman who noticed a slowly growing, cutaneous nodule on the left breast. Local excision of the lesion was performed and histology allowed to find a sinusoidal hemangioma. No recurrence was noticed. Conclusion. The very few reports of such a lesion in the literature reflect either rarity of such lesions or unfamiliarity of this subset among the pathologists.